Trunk Injection with Insecticides Manages Xylotrechus chinensis (Chevrolat) (Coleoptera: Cerambycidae) - Nickolas G. Kavallieratos; Maria C. Boukouvala; Anna Skourti; Erifili P. Nika; Georgios Th. Papadoulis (Insects, 2022)
Xylotrechus chinensis (Chevrolat) (Coleoptera: Cerambycidae) is a serious wood-boring insect of mulberry trees (Morus spp.). Larvae of this species enter the trunk of the tree and feed on woody tissues. Xylotrechus chinensis is endemic in several Asian countries, while, in the last decade, it invaded Europe. In the present work, we evaluated trunk injection against this pest. The systemic insecticides fipronil, imidacloprid, and spirotetramat were used in the trials. Abamectin was used as a positive control since it has been found to be effective for the management of X. chinensis. Imidacloprid and fipronil proved to be highly effective against this species in both years (9.5 and 12.1 exit holes/tree in 2021, 5.0 and 8.8 exit holes/tree in 2022, respectively), while spirotetramat was the least effective. The lowest mean number of exit holes was recorded when abamectin was applied in both years (4.7 exit holes/tree in 2021 and 3.3 exit holes/tree in 2022). The percentage of exit holes was reduced by 76.1, 71.8, and 85.6% in trees treated with imidacloprid, fipronil, and abamectin, respectively, after two years of application, while spirotetramat caused a 37.4% reduction. Trunk injection with imidacloprid, fipronil, and abamectin could be used against X. chinensis for long-term control of mulberry trees.